Early enteral levetiracetam in diazepam‐resistant convulsive status epilepticus. Issue 6 (12th August 2016) - Shibata, Naoaki; Yonemitsu, Takafumi; Ueda, Kentaro; Tanaka, Masaoh; Nakashima, Tsuyoshi; Kawazoe, Yu; Yamazoe, Shinji; Iwasaki, Yasuhiro; Kato, Seiya
Abstract: Background: Levetiracetam is used intravenously as an emergent initial and urgent control therapy for acute convulsive status epilepticus. However, the efficacy of early enteral levetiracetam has not been confirmed in cases of benzodiazepine‐resistant convulsive status epilepticus. Aim: We evaluated the efficacy and safety of levetiracetam administration through a nasogastric tube in acute convulsive status epilepticus resistant to intravenous diazepam. Methods: In a single‐center prospective study, we assigned convulsive status epilepticus patients previously treated with intravenous diazepam (20 mg maximum) to either the terminated seizure group or continued seizures group. In both groups, the patient received 1500 or 3000 mg of levetiracetam enterally within 30 min after diazepam according to primary seizure cessation, and the daily enteral levetiracetam maintenance dose after admission was set to the same amount as the initial levetiracetam dose. The primary end‐point was the efficacy of enteral levetiracetam within 30 min after diazepam in the diazepam‐resistant group. Results: In eight of nine diazepam‐resistant patients (88.9%) and 11 of 12 (91.7%) diazepam‐responders, the seizures were controlled within 30 min after diazepam ( P = 1.00), and the 3‐day seizure freedom rate was equivalent in the two groups (88.9 vs 83.3%, P = 1.00). Less than 10% of the overall patients had levetiracetam‐related mild side‐effects (no differences between the two groups). Conclusions: Throughout the 3‐day acute stage, early enteral levetiracetam just after intravenous diazepam is effective for both primary control of ongoing seizures and preventing seizure recurrence, even in diazepam‐resistant convulsive status epilepticus, without serious side‐effects.